Syntactical Analysis of Simple Sentences Found in Jakarta Post Website’s Article - Samuel Prihambodo Quasimus; Putu Devi Maharani (CV Wahana Publikasi, 2023)
The purpose of this study is to identify the types of simple sentences and describe the constituent structure of the process of transformation used in simple sentence found in Jakarta Website’s article. The research is descriptive qualitative research. The data used in this research were taken from online news articles published on the Jakarta Post website. The sentences were taken from the articles posted on 8 July 2022 entitled “G20 FMM: Opening Speech of Indonesian Foreign Minister”. The analysis was oriented to syntactic analysis. In analyzing the data, the types of simple sentence were identified and after that described the process of transformation of simple sentence used in Jakarta Post News Website’s Article. The result of the study shows there are the types of simple sentence found in Jakarta Post News Website’s Article. Simple sentence structure types were identified in the data, which was then categorized, displayed, and described. The results of the tenses studied are 10 (ten) sentences in a data source that belongs to simple sentence structures.